Increasing levels of de-oiled wet distillers grains in feedlot diets on nutrient digestibility, ruminal fermentation and microbiology - Tomaz, Lais de Aquino [UNESP]; Niehues, Maria Betania [UNESP]; Baldassini, Welder Angelo [UNESP]; Castagnino, Pablo [UNESP]; Amaral Bertoco, Joao Pedro [UNESP]; van Cleef, Eric; Ezequiel, Jane [UNESP]; Arrigoni, Mario de Beni [UNESP]; Martins, Cyntia L. [UNESP]; Neto, Otavio R. Machado [UNESP] (Elsevier B.V., 2021)
The supply of wet distillers grains (WDG) has been growing in Brazil, with the increase in corn ethanol production. However, little is known about de-oiled corn WDG on nutrient digestibility, ruminal fermentation and microbiology of beef cattle. Thus, the aim of the study was to evaluate the effects of the increasing levels of de oiled WDG replacing soybean meal and corn on dry matter (DM) intake, total tract digestibility, ruminal short chain fatty acids and microbiology. Eight ruminally cannulated Nellore bulls (BW = 453 ? 32 kg) were allocated on individual pens and distributed in 4 treatments with 0, 150, 300 and 450 g de-oiled WDG/kg DM in a 4 ? 4 replicated Latin square design. The experimental period lasted 112 days, divided into 4 periods of 28 days (14 days of adaptation plus 14 days of sampling). The DM, organic matter and ether extract intake increased quadratically (P < 0.05), and were greater in animals fed 300 g/kg WDG. Intake and digestibility of crude protein and neutral detergent fiber increased, however, intake and digestibility of non-fiber carbohydrates decreased linearly (P< 0.05) with increasing levels of de-oiled WDG.Gross energy (GE) and digestible energy (DE) intake were quadratically affected by the treatments, whereby animals fed 300 g/kg WDG in the diet showed greater (P < 0.05) GE and DE intake. Moreover, propionate and butyrate concentration increased linearly (P< 0.05) in animals fed de-oiled WDG, which could be associated to greater (P< 0.10) relative abundance of Selonomonas ruminantium, resulting in higher ruminal pH in these animals. Therefore, the inclusion of de-oiled WDG might be used as replacement of soybean meal and ground corn in high concentrate diets of Nellore cattle without compromising ruminal fermentation and nutrient digestibility.
Keywords: Bos indicus; Corn by-product; Feedlot; Metabolism; Zebu cattle